Mengapa Wajib Pajak Berminat Menggunakan Jasa Konsultan Pajak? - Nafisah Novalia; Antin Okfitasari; Rosyid Nur Anggara Putra; Ahmad Pauyan (Jurnal Akuntansi dan Pajak, 2022)
This study aims to obtain empirical evidence to determine the variables that affect why the taxpayer’s using tax consultants. The independent variables in this study are knowledge, tax consultant perceptions, tax sanctions, taxpayer motivation, and tax incentives. The dependent variable in this study is the interest in using the services of a tax consultant. The data in this study are primary data obtained from a questionnaire sample of 83 individual taxpayers in the Solo Raya area, using the purposive sampling method. The data analysis technique used multiple linear, the data was processed using SPSS 22. The results of the analysis showed that knowledge, perception of tax consultants, tax incentives, and motivation of taxpayers influenced the interest in using tax consultant services. However, tax sanctions do not affect interest in using the services of a tax consultant.